2009
DOI: 10.1063/1.3121324
|View full text |Cite
|
Sign up to set email alerts
|

A diabatic three-state representation of photoisomerization in the green fluorescent protein chromophore

Abstract: We give a quantum chemical description of the photoisomerization reaction of green fluorescent protein (GFP) chromophores using a representation over three diabatic states. Photoisomerization leads to non-radiative decay, and competes with fluorescence in these systems. In the protein, this pathway is suppressed, leading to fluorescence. Understanding the electronic states relevant to photoisomerization is a prerequisite to understanding how the protein suppresses it, and preserves the emitting state of the ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(127 citation statements)
references
References 93 publications
5
122
0
Order By: Relevance
“…The fact that SA3-CAS(4,3) solutions with the same structure can be found for these distinct molecules suggests that the solutions are stable, and that they are a general feature of dyes from this class. 45,47,48 Benchmark studies 49,50 have shown that the excitation energies of anionic GFP chromophore models calculated with multireference perturbation theory and SA-CASSCF models are not sensitive to basis set or active space size within a range of 0.2 eV, which is within quoted reliability limits 43,51,52 of such models. The systems studied here should be easier to deal with than this, because they are all cations.…”
Section: A Computationsmentioning
confidence: 76%
See 3 more Smart Citations
“…The fact that SA3-CAS(4,3) solutions with the same structure can be found for these distinct molecules suggests that the solutions are stable, and that they are a general feature of dyes from this class. 45,47,48 Benchmark studies 49,50 have shown that the excitation energies of anionic GFP chromophore models calculated with multireference perturbation theory and SA-CASSCF models are not sensitive to basis set or active space size within a range of 0.2 eV, which is within quoted reliability limits 43,51,52 of such models. The systems studied here should be easier to deal with than this, because they are all cations.…”
Section: A Computationsmentioning
confidence: 76%
“…This time scale separation is a natural consequence of the chemical structure of the dyes. The occurrence of similar self-consistent field solutions for these dyes 33 and others 45,48 is equally a consequence of the common chemical structure.…”
Section: A General Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference CASSCF wave functions were optimized using three-state averaging with the (4e,3o) active space, which provides a reliable description of twisting of the bridge bond. 69,79 The structures and the energy diagram for these geometries are shown in Figure 5. The twisted geometries optimized on the first excited state were found to be lower in energy than the Franck-Condon point by 0.38 and 0.14 eV for the I-and P-twisted minima, respectively.…”
Section: Conical Intersections Of Phbdimentioning
confidence: 99%